2016
DOI: 10.3168/jds.2016-11239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk replacer program on calf performance and digestion of nutrients in dairy calves to 4 months of age

Abstract: Calves fed >0.7 kg of dry matter from milk replacer (MR) typically have greater growth preweaning but lower growth postweaning. This is partially explained by lower digestibility of starter due to less development of the rumen at and after weaning; however, it is unclear when digestibility matures postweaning to levels typical of mature ruminants. Thus, we fed Holstein calves (initially 2 to 3 d of age) 3 MR programs (MOD = 0.66 kg daily for 39 d, and then 0.33 kg daily for 3 d, n = 15 calves; HIMOD = 0.88 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
61
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 36 publications
(52 reference statements)
11
61
2
Order By: Relevance
“…This was also evident when MR were fed at the same maximum rates in 2 different studies by Dennis et al (2017Dennis et al ( , 2018. Similarly, Hill et al (2016b) reported similar 112-d BW and hip width gains when MR were fed at 0.66 kg/d and weaning occurred at 42 d compared with feeding up to 1.1 kg/d and weaning at 49 d. When Hill et al (2016a) fed calves up to 1.31 kg/d and weaned at 49 d, 112-d BW gain appeared to be slightly greater for calves fed 1.31 kg/d versus calves fed 0.66 kg/d and weaned at 49 d, but 112-d hip width gain appeared slightly less for calves fed 1.31 kg/d.…”
Section: Effects Of Feeding Rate On Performance and Digestibilitymentioning
confidence: 61%
See 2 more Smart Citations
“…This was also evident when MR were fed at the same maximum rates in 2 different studies by Dennis et al (2017Dennis et al ( , 2018. Similarly, Hill et al (2016b) reported similar 112-d BW and hip width gains when MR were fed at 0.66 kg/d and weaning occurred at 42 d compared with feeding up to 1.1 kg/d and weaning at 49 d. When Hill et al (2016a) fed calves up to 1.31 kg/d and weaned at 49 d, 112-d BW gain appeared to be slightly greater for calves fed 1.31 kg/d versus calves fed 0.66 kg/d and weaned at 49 d, but 112-d hip width gain appeared slightly less for calves fed 1.31 kg/d.…”
Section: Effects Of Feeding Rate On Performance and Digestibilitymentioning
confidence: 61%
“…The substitution of starter intake for milk or MR is a relatively small amount of total DMI (<15 kg) over the first 4 mo of a calf's life. However, the delay in starter intake can slow rumen development and reduce starter digestibility pre-and postweaning (Terré et al, 2007a,b;Hill et al, 2010Hill et al, , 2016b. Reduced postweaning digestion can also last 4 wk or more (Hill et al, 2016b;Dennis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During weaning, starter consumption rapidly increases for calves fed high amounts of milk, whereas calves receiving 0.7 kg/d of DM or less from milk gradually increase starter consumption through the preweaning period. Lack of transitional feeding behaviors can delay rumen development, resulting in reduced starter digestibility for at least 4 wk after weaning (Terré et al, 2007;Osorio et al, 2012;Hill et al, 2013Hill et al, , 2016b. For example, calves allotted increasing amounts of pasteurized whole milk using computerized autofeeders averaged less than 0.1 kg/d starter intake up to 6 wk of age when fed 8, 10, or 12 L/d, whereas starter intake averaged 0.3 kg/d for calves allotted 6 L/d (Rosenberger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the disap-pearance of starch in the digestive tract was essentially complete. Quigley et al (2019a, b) conducted an analysis of 3 studies (Hill et al, 2016b;Dennis et al, 2018a;Quigley et al, 2018) using individual digestibility measurements (n = 207). Multiple modeling approaches were used (Quigley et al, 2019a), including linear mixed models, exponential models, and broken-line regression models.…”
mentioning
confidence: 99%